Case report: A case of holocarboxylase synthetase deficiency with respiratory tract as the initial symptom - Zou, Haiying; Yang, Li; Zhang, Renlong; Qin, Yao (Frontiers in Genetics, 2024)
IntroductionHolocarboxylase synthetase deficiency (HLCSD) is a rare autosomal recessive genetic disorder caused by mutations in the holocarboxylase synthetase (HLCS) gene, which affects multiple systems. Common clinical manifestations include metabolic acidosis, rash, feeding difficulties, and growth retardation, with predominant involvement of the nervous system, skin, and hair. However, respiratory symptoms as the initial manifestation are relatively rare.Case PresentationWe report the case of a 1 year and 4-month-old Chinese male patient who presented with a 2-day history of cough, followed by half a day of wheezing and shortness of breath. Despite supportive treatment with antibiotics upon admission, the infant continued to experience rapid and deep breathing accompanied by groaning, and obvious wheezing. Blood gas analysis revealed metabolic acidosis that was difficult to correct. Blood tandem mass spectrometry showed elevations in C50H, C3, C4OH, and urine organic acid analysis revealed elevations in lactate, 3-hydroxybutyric acid, 3-hydroxyisovaleric acid, acetoacetic acid, 3-methylcrotonylglycine, and methylcitric acid. Genetic testing revealed two variants in the HLCS gene in the infant: NM_001352514: exon6: c.1088T>A: p.V363D variant and exon11: c.2434C>T: p.R812* heterozygous variant, resulting in HLCSD. Ultimately, the diagnosis of HLCSD was established, and oral biotin treatment achieved good clinical efficacy.ConclusionThis article summarizes the clinical data of a case of HLCSD in an infant, primarily presenting with respiratory symptoms. It provides a comprehensive summary of the etiology, diagnosis, and treatment, offering insights for the diagnosis of rare diseases by clinical physicians.